ANALISIS PELEPASAN HAK GUNA BANGUNAN DAN KUASA EKS KOBA TIN - Ara Hasna Khairunnisa; Meta Indah Budhianti (Reformasi Hukum Trisakti, 2022)
If the term of building use rights over state property expires and is not renewed, the property is returned to the state no later than one year later in a vacant state. However, PT Koba Tin has released rights and powers, including priority rights relating to building use rights 14 years after the rights expired, despite the fact that it has not seen any regulations regarding this topic being executed. The issue is formulated as follows: Is the transfer of the former PT Koba Tin's building use rights to the Regional Government in compliance with the relevant provisions, and does PT Koba Tin have the authority to transfer rights and powers connected to building use rights to the Regional Government? Normative research techniques, descriptive writing's characteristics, secondary data, data analysis techniques using a qualitative methodology, and deductive reasoning conclusions. The study's findings, analysis, and conclusion indicate that PT Koba Tin has not complied with the requirements of PP No. 40 of 1996, which call for giving up vacant land within a year. However, if PT Koba Tin has already reached an agreement with the regional government that no must to make reference to this clause; the surrender of rights and powers can still be carried out.